Consumers Satisfaction Level Towards Sustainable Practices of 5-Star Category Hotels of Mumbai ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Sustainability in the hospitality industry has gained increased importance with environmentally conscious consumers. The present study focusses on consumers’ satisfaction towards the sustainable practices of 5-star hotels in Mumbai. This study helps to understand how these hotels have managed to deal with environmental concerns like energy efficiency, water conservation, plastic reduction, etc. and thus help in improving the customer experience by matching the rising sustainability expectations. This research attempts to analyze consumers’ perception regarding sustainability in 5-star hotels and suggests implementable suggestions to hotel practitioners that can contribute toward customer satisfaction. Objective: The primary objectives of this research were: To examine the consumers’ satisfaction level with sustainable practices at 5-star hotels in Mumbai. To suggest measures for hotel professionals to improve consumer satisfaction with these sustainable practices. Methodology: To fulfill the objectives of the study, a descriptive research design was adopted. Data were collected during August 2024 through convenience sampling in respect to diversified visitor responses towards the 5-star hotels of Mumbai. Online surveys through social media and e-mails were adopted as data gathering instruments, wherein a total of 270 questionnaires were issued and 165 were received. Only 156 were considered for final analysis. It contained two sections: a demographic data questionnaire and a questionnaire assessing consumer satisfaction with sustainable practices. The description statistics and specifically the technique of central tendency, were utilized to determine the weighted means and rankings for each of the practices surveyed. Results: The most appreciated were energy efficiency (3.87) and water conservation (3.56) by guests as being highly satisfactory. Plastic reduction (3.38) as well as the sourcing of sustainable food (3.12) followed even though reactions towards these were varied. Practices such as waste management, sustainable linen reuse and environment friendly toiletries were rated only moderately satisfactory; however, sub-areas including local community engagement, transparency and carbon emissions reduction were not rated satisfactorily, where there is room for improvement with better communication and visibility of the sustainability efforts. Conclusion: Energy efficiency and water conservation are highly appreciated by guests; however, other practices such as waste management, linen reuse and eco-friendly toiletries are not communicated sufficiently. Sustainability activities such as involvement in the local community and reduction of carbon also require more visibility for consumer satisfaction. Hotels should therefore focus on increasing guest engagement and transparency in sustainability initiatives to fulfill guest expectations within luxury standards.
Keywords: Consumers; satisfaction level; sustainable practices; 5-star hotels; Mumbai